COMMUNICATION SKILLS TRAINING FOR HEALTH WORKERS TO IMPROVE SERVICES OF PUBLIC HEALTH CENTER AT SIDOARJO - Saptyasari, Andria; Titik Puji Rahayu; Ratih Puspa; Santi Isnaeni; Suko Widodo; Dina Septiani; Rani Sukma Ayu Suteja; Mytha Eliva Veritasia; Intan Fitranisa; Yuyun W. I. Surya; Angga Prawadika Aji; Irfan Wahyudi; Rachmah Ida; Yayan Sakti Suryandaru; Liestianingsih D (Universitas Airlangga, 2025)
The effective communication is crucial for providing good service at the Community Health Center (Puskesmas). One major issue that can lead to patient dissatisfaction is the communication skills of health workers. When these workers struggle to communicate well, patients may feel poorly served and find it hard to understand their health conditions and care instructions. To address this problem, the Communication Department of FISIP UNAIR organized a training called